Compensating for excess micromotion of ion crystals *Project supported by the National Basic Research Program of China (Grant Nos. 2012CB821301 and 2010CB832803), the National Natural Science Foundation of China (Grant Nos. 11004222 and 91121016), and the Fund from Chinese Academy of Sciences. (August 2015) - Du, Li-Jun; Chen, Ting; Song, Hong-Fang; Chen, Shao-Long; Li, Hai-Xia; Huang, Yao; Tong, Xin; Gao, Ke-Lin; Guan, Hua
Abstract A new method of compensating for the excess micromotion along two directions in three-dimensional Coulomb crystals is reported in this paper; this method is based on shape control and optical imaging of a Coulomb crystal in a sectioned linear ion trap. The characteristic parameters, such as the ion numbers, temperatures, and geometric factors of different ion crystals are extracted from the images and secular motion excitation spectra. The method of controlling the shape of the ion crystals can be used in cold ion experiments, such as sympathetically cooling, structural phase transitions, and selective-control of ions, etc.